Subtypes of Hepatitis B Antigen in Blood Donors and Post-transfusion Hepatitis: Clinical and Epidemiological Aspects. Issue 5845 (13th January 1973) - Iwarson, Sten; Magnius, Lars; Lindholm, Annika; Lundin, Per
Abstract : Subtyping of hepatitis B antigen (HBA) in blood donors revealed subtype ad in 56% while patients with icteric post-transfusion hepatitis from the same centre showed subtype ay in the majority of the cases (75%). Donors with subtype ad in serum were mostly asymptomatic long-term carriers of the antigen with normal liver function (83%), while 70% of donors with subtype ay in serum had signs of acute or chronic liver disease. Healthy long-term carriers of HBA seem to present little risk of transmitting hepatitis irrespective of subtype. It is, however, possible that these differences in blood donors with subtype ad and patients with post-transfusion hepatitis with subtype ay might reflect epidemiological circumstances rather than biological differences in the two viral strains.